Kichik maktab yoshida o’quvchilarni maktab ta’limiga moslashtirishning ayrim masalalari - Yulchiyev Sobirali (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article describes some aspects of the school psychologist's work with first-grade students' psychological adaptability to school, as well as low-assimilation students.